Association of modifiable risk factors and telomere length with five neuroendocrine neoplasms: a bidirectional Mendelian randomization study - Xujia Li; Lingli Huang; Yue Yan; Yuming Rong; Xuxian Chen; Mengge Gao; Jinsheng Huang (Discover Oncology)
Abstract Background  The timely recognition of modifiable risk factors holds paramount importance in tumor prevention. We aimed to scrutinize the causal relationships between a spectrum of genetically modifiable risk factors and five distinct neuroendocrine neoplasms. Methods A bidirectional two-sample Mendelian randomization (MR) analysis was employed to elucidate the causal relationships between 41 potential risk factors and five neuroendocrine neoplasms. Results Height, obesity class 1, 2, and 3, overweight, waist-to-hip ratio, waist circumference, and serum uric acid were identified as factors associated with an augmented risk of colorectal neuroendocrine neoplasms (all p < 0.05). Conversely, a negative correlation was observed between fasting glucose and the risk of colorectal neuroendocrine neoplasms (p = 0.031). Platelet count exhibited a negative correlation with lung neuroendocrine neoplasms (p = 0.02). Moreover, the waist-to-hip ratio demonstrated a negative association with the risk of pancreatic neuroendocrine neoplasms. Atrial fibrillation, mean cell heamoglobin, and mean cell volume were positively associated with the risk of small intestine neuroendocrine neoplasms. In gastric neuroendocrine neoplasms, obesity class 1 and 2, overweight, and telomere length were implicated in their heightened risk. Following adjustment for multiple tests, obesity class 1 remained statistically significant to colorectal neuroendocrine neoplasms, and telomere length maintained significance in association with gastric neuroendocrine neoplasms. The outcomes of reverse MR suggested a bidirectional causal relationship between telomere length and gastric neuroendocrine neoplasms. Conclusion This study provided genetic evidence for the causal relationships between potentially modifiable risk factors and the risk of five neuroendocrine neoplasms. Therapeutic approaches to these factors may provide a basis for preventing neuroendocrine neoplasms.